Significance of CCL2, CCL5 and CCR2 polymorphisms for adverse prognosis of Japanese encephalitis from an endemic population of India. Issue 1 (December 2017) - Chowdhury, Purvita; Khan, Siraj
Abstract Japanese encephalitis (JE) is a major contributor for viral encephalitis in Asia. Vaccination programme has limited success for largely populated JE endemic countries like India and disease exposure is unavoidable. Involvement of chemokines and its co-receptors for adverse prognosis of JE have been documented bothin vitro andin vivo . Identification of the genetic predisposing factor for JE infection in humans is crucial but not yet established. Therefore, we investigated the association of single nucleotide polymorphisms (SNPs) in chemokines (CCL2 andCCL5 ) and its co-receptors (CCR2 andCCR5 ) with their protein level for JE. The study enrolled 87 symptomatic JE cases (mild: severe = 24:63) and 94 asymptomatic controls. Our study demonstrated thatCCL2 (rs1024611G), CCL5 (rs2280788G) andCCR2 (rs1799864A) significantly associated with JE (Odds ratio = 1.63, 2.95 and 2.62, respectively and P = 0.045, P = 0.05 and P = 0.0006, respectively). The study revealed that rs1024611G allele was associated with elevated level of CCL2. CCL5 elevation associated with JE mortality having a Cox proportional hazard of 1.004 (P = 0.033). In conclusion, SNPs of chemokineviz .CCL2 (rs1024611G) and its receptorCCR2 (rs1799864A) significantly associated with JE which may serve as possible genetic predisposing factor and CCL5 protein level may act as marker for disease survival.